(untitled) (Research, Society and Development, 2021)
The aim of this article is to present a clinical case of guided bone regeneration using platelet-rich fibrin and L-PRF leukocytes. A 72-year-old female patient, ASA II, came to the dental clinic with a chief complaint of severe mobility of tooth 24 (FDI). After anamnesis, clinical and tomographic examination we observed a marked loss of buccal and apical bone plate of the tooth. The treatment plan chosen was exodonty, immediate implant installation and guided bone regeneration. The integrity of the bone substitute in the grafted region, as well as the peri-implant health and integrity, were observed in this clinical case.